PENGARUH SERVICE QUALITY TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION DAN AIRLINE IMAGE SEBAGAI PEMEDIASI (Survei pada Pengguna Jasa Maskapai Penerbangan Garuda Indonesia Airline di Kota Surakarta dan DIY) - Ernawati, Anna Hariyatiningsih, Alwi Suddin & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2016)
This research aims to analyses (1) significance of the effect service quality on customer satisfaction (2) significance of the effect service quality on the airline image (3) significance of the effect service quality on customer loyalty (4) significance of the effect customer satisfaction on customer loyalty (5) significant of the effect airline image on customer loyalty (6) the effect of service quality on customer loyalty mediated by customer satisfaction (7) the effect of service quality on customer loyalty mediated airline image. Location of this research in the region at Surakarta and DIY, using samples of 100 customers of the Garuda Indonesia Airline with purposive sampling technique. Data collecting with questionnaire technique through validity and reliability test. To test the hypothesis using path analysis. The result shows that (1) service quality has significance effect on customer satisfaction, so the hypothesis 1 accepted; (2) service quality has significance effect on the airline image, so the hypothesis 2 accepted (3) service quality has significance effect on customer loyalty, so the hypothesis 3 accepted; (4) customer satisfaction has significance effect on customer loyalty, so the hypothesis 4 accepted (5) airline image has significance effect on customer loyalty, so the hypothesis 4 accepted; (6) the effect of service quality on customer loyalty mediated by customer satisfaction, so the hypothesis 6 accepted; (7) the effect of service quality on customer loyalty mediated airline image, so the hypothesis 7 accepted. Keywords: service quality, customer satisfaction, airline image, customer loyalty